Modified Reporting of Positive Urine Cultures to Reduce Inappropriate Treatment of Asymptomatic Bacteriuria Among Nonpregnant, Noncatheterized Inpatients: A Randomized Controlled Trial. (28th May 2018) - Daley, Peter; Garcia, David; Inayatullah, Raheel; Penney, Carla; Boyd, Sarah
Abstract : DESIGN: We conducted a randomized, parallel, unblinded, superiority trial of a laboratory reporting intervention designed to reduce antibiotic treatment of asymptomatic bacteriuria (ASB). METHODS: Results of positive urine cultures from 110 consecutive inpatients at 2 urban acute-care hospitals were randomized to standard report (control) or modified report (intervention). The standard report included bacterial count, bacterial identification, and antibiotic susceptibility information including drug dosage and cost. The modified report stated: "This POSITIVE urine culture may represent asymptomatic bacteriuria or urinary tract infection. If urinary tract infection is suspected clinically, please call the microbiology laboratory … for identification and susceptibility results." We used the following exclusion criteria: age <18 years, pregnancy, presence of an indwelling urinary catheter, samples from patients already on antibiotics, neutropenia, or admission to an intensive care unit. The primary efficacy outcome was the proportion of appropriate antibiotic therapy prescribed. RESULTS: According to our intention-to-treat (ITT) analysis, the proportion of appropriate treatment (urinary tract infection treated plus ASB not treated) was higher in the modified arm than in the standard arm: 44 of 55 (80.0%) versus 29 of 55 (52.7%), respectively (absolute difference, −27.3%; RR, 0.42; P = .002; number needed to report for benefit, 3.7). CONCLUSIONS: Modified reporting resulted in a significant reduction in inappropriate antibiotic treatment without an increase in adverse events. Safety should be further assessed in a large effectiveness trial before implementation TRIAL REGISTRATION. clinicaltrials.gov#NCT02797613 Infect Control Hosp Epidemiol 2018;814–819